The single-cell atlas of the epididymis in mice reveals the changes in epididymis function before and after sexual maturity - Zhang, Jiaxin; Xie, Ye; Wang, Xiaoyan; Kang, Yafei; Wang, Chuxiong; Xie, Qinying; Dong, Xinyi; Tian, Yonghong; Huang, Donghui (Frontiers in Cell and Developmental Biology, 2024)
The epididymis is important for sperm transport, maturation, and storage. The head and tail of the epididymis of 5-week-old and 10-week-old C57 BL / 6J male mice were used for single-cell sequencing. single-cell transcriptome sequencing to map different cell populations in the epididymal epithelium, identifying 10 cell types including main, basal, and narrow/clear cells. Next, we performed cell subgroup analysis, functional enrichment analysis, and differentiation potential prediction on principal cells, clear cells, and basal cells. Our study indicates that the principal cells are significantly involved in sperm maturation, as well as in antiviral and anti-tumor immune responses. Clear cells are likely to play a crucial role in safeguarding sperm and maintaining epididymal pH levels. Basal cells are implicated in the regulation of inflammatory and stress responses. The composition and functions of the various cell types within the epididymis undergo significant changes before and after sexual maturity. Furthermore, pseudo-temporal analysis elucidates the protective and supportive roles of epididymal cells in sperm maturation during sexual maturation. This study offers a theoretical framework and forecasts for the investigation of epididymal sperm maturation and epididymal immunity.